2002
DOI: 10.1093/carcin/23.3.419
|View full text |Cite
|
Sign up to set email alerts
|

CagA status of Helicobacter pylori infection and p53 gene mutations in gastric adenocarcinoma

Abstract: Infection with Helicobacter pylori (H. pylori) increases stomach cancer risk. Helicobacter pylori strains with the cag pathogenicity island (PAI) induce more severe inflammation in the gastric epithelium and are more strongly associated with stomach cancer risk than strains lacking the PAI. We examined whether the prevalence of somatic p53 mutation in gastric adenocarcinoma differed between subjects with and without infection with CagA(+) (a marker for the PAI) H. pylori strains. DNA from 105 microdissected tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 31 publications
2
38
0
4
Order By: Relevance
“…Kodama et al [43] have suggested an accumulation of wild-type p53, especially in the H pylori infected mucosa probably due to the H pylori-induced DNA damage. The present study shows the highest frequency of p53 mutation in the groups with H pylori infection, especially among the cagA+ cases, corroborating previous studies [16,3,4] . The high percentage of p53 mutation in EBV-associated and EBV-negative gastric carcinomas was observed in our study which was also demonstrated in other studies, demonstrating that the p53 mutation is a relevant alteration in gastric carcinogenesis independent of the infection [15,16,43] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Kodama et al [43] have suggested an accumulation of wild-type p53, especially in the H pylori infected mucosa probably due to the H pylori-induced DNA damage. The present study shows the highest frequency of p53 mutation in the groups with H pylori infection, especially among the cagA+ cases, corroborating previous studies [16,3,4] . The high percentage of p53 mutation in EBV-associated and EBV-negative gastric carcinomas was observed in our study which was also demonstrated in other studies, demonstrating that the p53 mutation is a relevant alteration in gastric carcinogenesis independent of the infection [15,16,43] .…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of H pylori infection (94.4%) was higher than previous studies, where it ranged from 34.1% to 92%. These differences can be due to: (a) the sensitivity of the screening technique, since most previous studies used serology, rapid urease test and/or histological evaluation; (b) and the fact that these studies were performed in different world regions and it is known that the H pylori infection is more frequent in developing countries [8,16,[22][23][24] . On the other hand, EBV was detected in 8.45% of our cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although diffuse-type gastric cancer is strongly associated with infection with H. pylori, it is equally associated with strains containing the cag PAI and those lacking it (42). Individuals infected with H. pylori strains containing the cag PAI have also been shown to have an increased likelihood of having mutations in the gene encoding p53 (44). This correlates with the observation that p53 +/-mice transgenic for the lacI gene (which enables researchers to measure the rate of genetic mutations) that are chronically infected with Helicobacter felis have a cumulative increase in gastric tissue mutations and ostensibly an increased cancer risk (45).…”
Section: Role Of Bacterial Virulence Factors In H Pylori Persistencementioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18)(19) In terms of epigenetic alterations, reduced expression of acetylated histone H4 or DNA methylation of CDH1 and RAR-β have been shown to be correlated with tumor invasiveness and the tumor metastasizing potential. (20,21) On the other hand, the recent introduction of the microarray technology has enabled significant genes to be identified almost throughout the genome using a hypothesis-free approach.…”
mentioning
confidence: 99%